Bioactive Peptides Against Fungal Biofilms - Oshiro, Karen G. N.; Rodrigues, Gisele; Monges, Bruna Estéfani D.; Cardoso, Marlon Henrique; Franco, Octávio Luiz (Frontiers in Microbiology, 2019)
Infections caused by invasive fungal biofilms have been widely associated with high morbidity and mortality rates, mainly due to the advent of antibiotic resistance. Moreover, fungal biofilms impose an additional challenge, leading to multidrug resistance. This fact, along with the contamination of medical devices and the limited number of effective antifungal agents available on the market, demonstrates the importance of finding novel drug candidates targeting pathogenic fungal cells and biofilms. In this context, an alternative strategy is the use of antifungal peptides (AFPs) against fungal biofilms. AFPs are considered a group of bioactive molecules with broad-spectrum activities and multiple mechanisms of action that have been widely used as template molecules for drug design strategies aiming at greater specificity and biological efficacy. Among the AFP classes most studied in the context of fungal biofilms, defensins, cathelicidins and histatins have been described. AFPs can also act by preventing the formation of fungal biofilms and eradicating preformed biofilms through mechanisms associated with cell wall perturbation, inhibition of planktonic fungal cells’ adhesion onto surfaces, gene regulation and generation of reactive oxygen species (ROS). Thus, considering the critical scenario imposed by fungal biofilms and associated infections and the application of AFPs as a possible treatment, this review will focus on the most effective antifungal peptides described to date, with a core focus on antibiofilm peptides, as well as their efficacy in vivo, application on surfaces and proposed mechanisms of action.